1994
DOI: 10.1677/joe.0.1420311
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of intracellular progesterone and glucocorticoid receptors in the rabbit lung

Abstract: We have determined the presence and distribution of intracellular progesterone receptors (PRs) and glucocorticoid receptors (GRs) in the lung of adult female rabbits using immunohistochemistry. The effects of ovariectomy and administration of oestradiol benzoate (10 micrograms for 3 consecutive days) upon PR and GR immunoreactivity were also studied. The results demonstrated the presence of both steroid hormone receptors in the female rabbit lung. PR and GR immunoreactivity was predominantly nuclear and locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Our results on the regulation of PR gene expression by sex steroid hormones assessed by PR mRNA content in the lung are in line with data obtained at the protein level by immunohistochemical examination (Camacho-Arroyo et al 1994). It has been reported that oestradiol treatment of ovariectomized rabbits increased the number of PR-immunoreactive cells in the lung as compared with that of ovariectomized animals treated with vehicle alone (Camacho-Arroyo et al 1994).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results on the regulation of PR gene expression by sex steroid hormones assessed by PR mRNA content in the lung are in line with data obtained at the protein level by immunohistochemical examination (Camacho-Arroyo et al 1994). It has been reported that oestradiol treatment of ovariectomized rabbits increased the number of PR-immunoreactive cells in the lung as compared with that of ovariectomized animals treated with vehicle alone (Camacho-Arroyo et al 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, in the case of the uterus, no correlation was found between PR mRNA and PR protein content: on day 3 of pregnancy endometrial PR protein was not detectable in spite of the high PR mRNA content (Gutierrez-Sagal et al 1993). Although we observed a correlation between the effects of oestradiol on PR mRNA content and PR protein levels (Camacho-Arroyo et al 1994) in the lung, it is necessary to determine whether this correlation is maintained during early pregnancy in order to understand other aspects of PR gene expression regulation and the physiological meaning of PR changes in the lung during early pregnancy.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Three RARs and three RXRs have been demonstrated in the developing human lung (Rajatapiti et al, 2005). Our results complete the list of nuclear receptors previously described to be expressed in the rabbit developing lung including pregnane X receptor (Savas et al, 2000), glucocorticoid receptor (GR) (Hummelink and Ballard, 1986), androgen receptor (Giannopoulos and Smith, 1982), thyroid receptor (TR) (Ballard et al, 1984), progesterone receptor (Camacho-Arroyo et al, 1994) and peroxisome proliferator activated receptor (Michael et al, 1997). In both humans (Rajatapiti et al, 2005) and rabbits, developing lungs express receptors TR, RAR, RXR and GR.…”
Section: Discussionsupporting
confidence: 84%